What is consumption, where has it been going, and does it still matter? - Evans, David M (The Sociological review (Keele), 2019)
This article considers the relationships between consumption, the environment, and wider sociological endeavour. The current vogue for applying theories of practice to the policy domain of ‘sustainable consumption’ has been generative of conceptual renewal, however the field now sits closer to the applied environmental social sciences than to the sociology of consumption. The analysis proceeds via a close reading of the intellectual currents that have given rise to this situation, and it identifies a number of interrelated issues concerning conceptual slippage and the exclusion of core disciplinary concerns. Accordingly a more suitable definition of consumption is offered, an agenda for re-engaging with foundational approaches to consumer culture is established, and a renewal and reorientation of critique is proposed. Working through and building on the contributions of practice theoretical repertoires, this article suggests that consumption scholarship offers a distinctive set of resources to discussions of current ecological crises and uncertain social futures. These are briefly described and the conclusion argues that consumption still matters.